2016
DOI: 10.4103/2347-5625.189813
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of physical, psychological, social, and spiritual intervention in breast cancer survivors: An integrative review

Abstract: Factors affecting the health outcomes of cancer patients have gained extensive research attention considering the increasing number and prolonged longevity of cancer survivors. Breast cancer survivors experience physical, psychological, social, and spiritual challenges. This systematic literature review aims to present and discuss an overview of main issues concerning breast cancer survivors after treatment. Treatment-related symptoms as well as psychosocial and spiritual aspects of breast cancer survivors are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 61 publications
0
36
0
1
Order By: Relevance
“…[2729303233] It should be kept in mind that people offering care to their spouses may suffer from social isolation and should be encouraged to share their experiences with their family and friends and people experiencing similar problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2729303233] It should be kept in mind that people offering care to their spouses may suffer from social isolation and should be encouraged to share their experiences with their family and friends and people experiencing similar problems.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the present study, several other studies have shown that changes in social life have a negative impact on both patients and their spouses, which has become more marked as the caregiving process is lengthened. [ 27 29 30 32 33 ] It should be kept in mind that people offering care to their spouses may suffer from social isolation and should be encouraged to share their experiences with their family and friends and people experiencing similar problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interview outline used during the interviews was developed by the research team mainly based on the systematic reviews of BCSs mental health outcomes and BCSs psychosocial needs [ 27 , 31 , 32 ]. Parts on experience of cancer, sources of stress, psychological changes, current coping strategies, and needs of BCSs in the reviews and the related literatures were used to construct the list of questions for the interview.…”
Section: Methodsmentioning
confidence: 99%
“…Expectations are closely related to the behavior intention or motivation and are likely to determine the subsequent action. Implementing supportive interventions in the therapeutic, emotional and social domains to meet BCSs’ expectations has been shown to help BCSs adopt positive coping strategies to manage or reduce stress and have a significant protective effect on their health [ 27 ].…”
Section: Introductionmentioning
confidence: 99%